A Model of Mixed Strategic Orientations Based on Environment in Achieving a Tough Performance of MSMEs - Darmanto Darmanto; Sri Wardaya; Lilis Sulistyani; Basuki Sri Rahayu (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
This study aims to design a model in achieving superior performance of MSMEs. The mixed strategic orientations of demography, economy and cultural values are used to design this model. The mixed strategic orientations consist of customer, competitor and innovation orientations. Demographic variables consist of age, experience and education. Economic variables consist of government, price, income and growth. Cultural value variables consist of Javanese, Chinese and Padang cultural values. Customer orientation variables have an antecedent variable that consist of entrepreneurship, reward and learning. The change orientation variable moderates the customer and competitor orientations to the innovation orientation. Variable of competitive advantage mediates customer and competitor orientations on MSMEs’ performance. The population of this study consists of food MSMEs in Central Java. The 750 samples are chosen with convenient sampling technique. Data analysis mrthod used the Cross-tab Analysis and Structural Equation Model (SEM). The result of this research is a model explaining that demography, economy and cultural values influence antecedent variables of customer orientation, dimension of strategic orientations and organizational performance. The antecedent variables affect customer orientation; the dimension of strategic orientations affects performance; Variable of change of capacity unmoderates customer and competitor orientations on innovation orientation. Variable of competitive advantage unmediates customer, innovation and competitor orientations on performance. An abstract should accompany each manuscript; it should be completely self-consistent (i.e., with no figure, table, equation or reference citations), not exceeding 250 words and written as a single paragraph.